Distributed MIMO coding scheme with low decoding complexity for future mobile TV broadcasting - Liu, M.; Hélard, M.; Crussière, M.; Hélard, J.-F. (Electronics letters, 2012)
A novel distributed space-time block code (STBC) for the next generation mobile TV broadcasting is proposed. The new code provides efficient performance within a wide range of power imbalance showing strong adaptivity to the single frequency network (SFN) broadcasting deployments. The new code outperforms existing STBCs with equivalent decoding complexity and approaches those with much higher complexities.